2004
DOI: 10.1016/j.orthres.2003.12.14
|View full text |Cite
|
Sign up to set email alerts
|

Early cementing does not increase debond energy of grit blasted interfaces

Abstract: A fracture mechanics based approach was used to determine the debond energy or fracture toughness of the stem-cement interface for a variety of conditions. The goals of the study were to determine if early cementing of stems increased the debond energy of grit blasted stem-cement interfaces and ifdebond energy was dependent on mold type. Early (2 min) and late (6 min) times of cementation were considered for two different grit blasted surface finishes (I6 and 60 grit, Ra = 5.7 or 2.3 pm). Specimen fabrication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…1,11,24 However, it appears that the debond strength can also depend to a great extent on the fabrication method. 18 Gap and pore formation is more likely to occur at the stem-cement interface when using grit-blasted stems when compared with satin finished stems. 20 These gaps could serve as initiation sites for debonding; the torsion experiment presented here was designed to simulate this effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,11,24 However, it appears that the debond strength can also depend to a great extent on the fabrication method. 18 Gap and pore formation is more likely to occur at the stem-cement interface when using grit-blasted stems when compared with satin finished stems. 20 These gaps could serve as initiation sites for debonding; the torsion experiment presented here was designed to simulate this effect.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with smooth stems, roughening of the stem surface results in an increase in debond strength 1, 11, 24. However, it appears that the debond strength can also depend to a great extent on the fabrication method 18. Gap and pore formation is more likely to occur at the stem–cement interface when using grit‐blasted stems when compared with satin finished stems 20.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 The adverse effect of porosity on PMMA fatigue life is reported in the literature: the pores across the cement mantle act as stress raisers and nucleation sites for microcracks. 6,[12][13][14] Mann et al 15 reported a negative effect of porosity on debond energy of the stem/cement interface. Interestingly, Topoleski et al 12 have suggested that bulk porosity can have a benefi-cial effect on the fracture properties of bone cement, hypothesizing that pores forming larger damage zones slow down crack propagation in the cement mantle as the energy at the crack tip is dispersed.…”
Section: Introductionmentioning
confidence: 99%